Dried flower powder combination of Clitoria ternatea and Punica granatum demonstrated analogous anti-hyperglycemic potential as compared with standard drug metformin: In vivo study in Sprague Dawley rats - Sachin P. Borikar, Nilesh G. Kallewar, Debarshi Kar Mahapatra, Nitin G. Dumore (Journal of Applied Pharmaceutical Science, 2018)
The diabetes mellitus type-2 (DMT-2) is among the highly escalating disease that is expected to affect nearly 400 million people across the globe by the end of 2030. In DMT-2, the control of post-prandial surge is the most imperative requirement for the management of metabolic disturbances. The inclined trend toward herbal-based medicine among the developing nations owing to their safety and reduced side-effects has compelled the researchers to explore the hidden potentials of herbs and shrubs of Mother Nature. The increasing interest of herbal products among the patient population has also revolutionized the traditional ethnopharmacological aspects. While processing toward the direction, the research involved yet unreported anti-hyperglycemic activity of two well-known Indian plants Clitoria ternatea (Family: Fabaceae) and Punica granatum (Family: Punicaceae). In the present study, the dried flower powder of C. ternatea and P. granatum was screened individually and in combination for their anti-hyperglycemic activity in alloxan-induced diabetic rat model employing the standard drug metformin hydrochloride. The research demonstrated that the combination of dried flower powder of C. ternatea and P. granatum exhibited a significant anti-hyperglycemic effect after 5 hours of oral administration. The phytoconstituents present in the plant material; primarily, the flavonoids and alkaloids play a crucial role in mediating the pharmacological activity. This study will open new perspectives of future research in developing novel herbal formulations for the management of diabetes mellitus at the clinical level.
Keywords: Hypoglycemic, Clitoria ternatea, Punica granatum, flower, powder, alloxan.